Predictors of physical activity to prevent osteoporosis based on extended Health Belief Model - Atoosa Solimanian; Shamsoddin Niknami; Ibrahim Hajizadeh; Davood Shojaeezadeh; Mahmoud Tavousi (Payesh, 2014)
Objective (s): The purpose of this study was to test predictors of physical activity to prevent osteoporosis using an adapted form of the Health Belief Model in a sample of women. Methods: This was a cross sectional study among women aged 30 years and over using a theory-based new instrument. In this methodological study, path analysis was used for testing predictors of a desired behavior (physical activity). Results: In all 240 women wer entered into the study. The results obtained form path analysis indicated that the data was fit with the extended Health Belief Model (χ2/df= 2.54, P < 0.0001, CFI = 0.94, GFI = 0.96, and RMSEA = 0.07). As such results showed that the model explained 48% of variances observed. Cues to action, Self-efficacy, and Self-regulation had the greatest effect on the behavior studied. Conclusion: The findings support the application of the extended Health Belief Model for prediciting a behavior change.